Architecture and the smart city - Figueiredo, Sergio M. (New York : Routledge, 2020)
"Increasingly the world around us is becoming 'smart.' From smart meters to smart production, from smart surfaces to smart grids, from smart phones to smart citizens. 'Smart' has become the catch-all term to indicate the advent of a charged technological shift that has been propelled by the promise of safer, more convenient and more efficient forms of living. Most architects, designers, planners and politicians seem to agree that the smart transition of cities and buildings is in full swing and inevitable. However, beyond comfort, safety and efficiency - how can 'smart design and technologies' assist to address current and future challenges of architecture and urbanism? Architecture and the Smart City provides an architectural perspective on the emergence of the smart city and offers a wide collection of resources for developing a better understanding of how smart architecture, smart cities and smart systems in the built environment are discussed, designed and materialized. It brings together a range of international thinkers and practitioners to discuss smart systems through four thematic sections: 'Histories and Futures', 'Agency and Control', 'Materialities and Spaces' and 'Networks and Nodes.' Combined, these four thematic sections provide different perspectives into some of the most pressing issues with smart systems in the built environment. The book tackles questions related to the future of architecture and urbanism, lessons learned from global case studies, challenges related to interdisciplinary research, and critically examines what the future of buildings and cities will look like"--
The Metaphor of the City as a Thinking Machine. A Complicated Relationship and its Backstory Sonja Hnilica (TU Dortmund, Germany) -- The Right to the (Smart) City, Participation and Open Data / Jonas Breuer, Nils Walravens, Shenja Van der Graaf, Ilse Marien (imec-SMIT, Vrije Universiteit Brussel, Belgium) -- Politics of sensing and listening / Dietmar Offenhuber (Northeastern University, United States), Sam Auinger (Independent Sound artist) -- Standing Out in a Crowd : Big Data to Produce New Forms of Publicness / Silvio Carta, Rebecca Onafuye (University of Hertfordshire, United Kingdom), Pieter de Kock (University of Lincoln, United Kingdom)
OCLC-licensed vendor bibliographic record.
Keywords: Architecture and technology; Smart cities; ARCHITECTURE / Criticism; ARCHITECTURE / Study & Teaching; ARCHITECTURE / History